CORRELATION BETWEEN THE NUTRITION ADEQUANCY LEVEL AND AEROBIC ENDURANCE OF MALE FUTSAL EXTRACURRICULAR PARTICIPANTS AT REJOSO 1 HIGH SCHOOL - Teja Windi Rangga; Sri Santoso Sabarini; Manshuralhudlori Manshuralhudlori (Universitas Sebelas Maret, 2021)
The male student of futsal extracurricular participants at SMA Negeri 1 Rejoso in 2020 experienced an average quality decrease after playing over 17 minutes on the second round of the game so the researcher suspected that it was related to the aerobic endurance possessed by students. Besides aerobic endurance, the nutrition adequancy level of each futsal extracurricular participants at SMA Negeri 1 Rejoso also have differences, starting from age, weight and height. The results of the observation conducted by researcher with extracurricular trainers, the researcher wants to correlate the nutrition adequancy level with the aerobic endurance of each student. The method used in this research is a quantitative method with correlational techniques using 2 variables, the nutrition adequancy level and aerobic endurance. The population in this study were 15 students. The Body Mass Index (BMI) used to determine the nutrition adequancy level of students, while Multistage Fitness Test (MFT) used to determine the aerobic endurance. The research was conducted in 2 repetitions. The results of the research are tested for reliability test, normality test and correlation test. The results showed that there is no significant correlation between the nutritional adequancy level and aerobic endurance of male students’ futsal extracurricular at SMA Negeri 1 Rejoso in 2020. Value (- 0,229) < (0,514) or p (sig) 0,413 > 0,05. There is other factor related to aerobic endurance such as aerobic exercise training factor.